Understanding the Qur'an : a reflection - Khan, Israr Ahmad (IIUM Press, 2006)
The Qur'an represents the last revelation from on high. It addresses the entire humanity, Muslims and non-Muslims, Jews and Christians, Arabs and non-Arabs, the sincere and the hypocrite, the friends and the opponents, the ypung and the old, the male and the female, the rich and the poor, the educated and the illiterate, the master and the slave, the king and the subject. It seeks to lead them to a blistful life in both the mundane world and in the hereafter. This relationship between the Qur'an and man entails the latter's visiting and understanding the former. But today the man is in a dilemma, knowing not how to grasp the original message of the Qur'an revealed fifteen centuries ago. He finds before him multitudes of Qur'anic commentaries that are, at times mutually conflicting with one another. He is very much keen to take a step forward towards the Qur'an but feels shy rather hesitant to do that due to his lack of confidence to identify a sound methodology of understanding the Qur'an. This book may be deemed as a modest attempts towards the quest for that sound methodology the application of which may ensure true understanding of the Qur'an.